Strategic Indicators in the Development of Original Medicinal Products in 2024: Analysis of Pipelines of International Pharmaceutical Leaders - L. S. Litvin; E. A. Kulikova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Major international pharmaceutical companies play a crucial role in the development of original medicines. To determine the directions for original medicines development in Russia, it is essential to analyze global trends and emerging weak signals (tendencies) — early indicators of future-significant innovations.OBJECTIVE. To identify trends and emerging weak signals that could shape pharmaceutical development in Russia through an analysis of the pipeline of original medicines being developed by global pharma leaders.MATERIALS AND METHODS. An analysis was conducted on the medicinal product development plans for 2024 of the 20 largest pharmaceutical companies globally, which have the highest research and development budgets. The focus was on original medicines scheduled for clinical trials Phase 1 from January to May 2024. A descriptive research approach was applied, based on retrospective analysis of secondary data. The study measured the number of original medicines under development, research directions, target classes, medicine types, and groups. Both quantitative and qualitative evaluations were used to identify key trends and tendencies (emerging weak signals) in pharmaceutical development of medicines.RESULTS. During the analyzed period, 17 out of 20 leading pharmaceutical companies-initiated Phase 1 trials for a total of 84 original medicines. The most active research areas included oncology, endocrinology and metabolism, cardiovascular system, and immunology. Notably, 40 medicines entered Phase 1 trials in oncology. The largest share (42%) of the medicines in development consists of high molecular weight molecules. Based on the number of medicines developed by multiple companies, trends were identified for the following medicine classes: “Large molecule” — bispecific antibodies (10 medicines, 5 developers); monospecific antibodies (8 medicines, 7 developers); antibody-drug conjugates (8 medicines, 3 developers); “Small molecule” — enzyme inhibitors (9 medicines, 6 developers); “Cell therapy” — CAR-T-based therapies (6 medicinal products, 2 developers).CONCLUSIONS. Current trends in targeted therapy development include the creation of bispecific antibodies and next-generation antibody-drug conjugates, alongside CAR-T therapies based on autologous T cells, predominantly for the treatment of malignant neoplasms. The study of multispecific antibodies is shaping a new direction in targeted cancer therapy. The development of low-molecular-weight enzyme inhibitors is establishing a trend in various therapeutic areas. Specifically, enzyme inhibitors targeting synthetic lethal vulnerabilities like WRN and PRMT5 are emerging as a key tendency in small-molecule medicine development for targeted cancer therapy.